(untitled) (Research, Society and Development, 2020)
Diabetes Mellitus (DM) is a disease characterized by causing dysfunction in glucose metabolism. Conduct a review that lists the beneficial effects of catechins present in green tea related to type 2 Diabetes Mellitus. The search for articles occurred by the association of keywords: green tea, catechins, type 2 diabetes mellitus and oxidative stress. The terms were searched in English and Portuguese from 2013 to 2018 on the basis of periodocos, Lilacs; Medline, pubmed, Web of Science and Scielo. Of the 20 articles found with the association of these keywords, 7 were selected. The beneficial effects of catechins in relation to Diabetes Mellitus 2 and their possible effective actions on the pathology in question were analyzed. It was observed that the catechins present in green tea have antioxidant properties, which can protect or reduce oxidative damage in diabetic patients, helping to control DM2 and other pathologies; Epigallocatechin-3-gallate (EGCG) was the catechin found in greater quantity and the one with the greatest benefit in relation to DM2. This review contributes to the discussions about the aid of green tea for the control of Diabetes Mellitus 2, it was observed that the catechins present in green tea have beneficial effects in relation to DM2 and that EGCG had greater biological activity, as well as having the highest concentration in the leaf of the Camellia Sinensis plant. It is worth mentioning the importance of conducting more clinical studies that evaluate the beneficial effects, and the pharmacological and biological activity of catechins in green tea in isolation.